DDoS attack detection mechanism in the application layer using user features - Bravo S. (2018)
The authors thank the National Council of Science,Technology and Technological Innovation (CONCYTEC)-Peru and Technical University of Cotopaxi for the partial funding of this work and Professor Angel H. Moreno for their contributions to this work